Effect of FUT3 gene silencing with miRNA on proliferation, invasion and migration abilities of human KATO-III gastric cancer cell line - Cai, Y-J; Zheng, X-F; Lu, C-H; Jiang, Q; Liu, Q; Xin, Y-H (Cellular and Molecular Biology, 2016)
This study investigated the effects of FUT3 gene expression inhibition with miRNA on the proliferation, invasion and migration abilities of KATO-III cells. KATO-III cells were transfected with plasmid pcDNAâ„¢6.2-GW/EmGFP-FUT3-miR(FUT3-miRNA) and negative control plasmid in mediation of liposome, respectively, using untransfected cells as blank controls. Forty-eight hours after transfection, FUT3 mRNA levels were tested by RT-PCR. Levels of sLeA proteins were assayed by Western blot. The effects of FUT3-miRNA on the proliferation, invasion and migration of KATO-III cells were determined by CCK8 testing and Transwell assays, respectively. Results indicate that the transfection of FUT3-miRNA may down-regulate sLeA protein expression on the surface of KATO-III cells, and significantly inhibit cell proliferation (p<0.05). As compared to the negative and blank control groups, the number of invasion and migration cells in the FUT3-miRNA group decreased significantly (each p<0.05). Experimental results indicate that the miRNA expression vector which targets the FUT3 gene can effectively inhibit the proliferation, migration and invasion abilities of KATO-III cells.